In Silico of Subject-Specific Progression of Knee Osteoarthritis: A Finite Element Analysis on Swing and Stance Phases - Ahmed Hasan Alsaqqaf, Aceel; Ramlee, Muhammad Hanif; Gan, Hong Seng; Nasution, Ahmad Kafrawi; Abdul Kadir, Mohammed Rafiq (International Journal of Integrated Engineering, 2025)
The clinical condition of joint pain and dysfunction induced by joint degeneration, osteoarthritis, affects more people than any other joint illness. Mechanical stress is a major contributor to the onset of osteoarthritis (OA). However, there is a difficulty of achieving direct quantitative measures of tissue behaviours during different grades of osteoarthritis and currently there is a lack of studies that explore the changes seen in cartilage effected by OA during swing and stance phases. Therefore, the purpose of this research is to look at the role of articular cartilage in the development of OA, as well as to evaluate and simulate the biomechanical behaviour of the knee joint under various boundary conditions by segmented knee joints from computed tomography datasets. Mimics software has been used to obtain the 3D model of the knee bones. In addition, the soft tissues were modelled using 3-matic software. Marc.Mentat software was used to correctly simulate the knee OA behaviour during the stance and swing phases for the nonlinear finite element analysis. During the stance and swing phases, the maximum von Mises stress and displacement on the femur, femoral cartilage, tibia, and tibial cartilage were collected for healthy, grade 1 and grade 2 osteoarthritis. The results reveal that when body weight load increased, so did stresses and displacements in articular cartilage and bones. This suggests that being overweight or obese may increase the risk of joint articular cartilage degeneration and osteoarthritis of the knee. In conclusion, based on the finite element analysis, the articular cartilage could be in a trouble if excessive forces are exerted towards it.